The vertebral heart scale on CT is correlated to radiographs in dogs. Issue 5 (20th June 2021) - Timperman, Lauren; Habing, Greg; Green, Eric
Abstract: The vertebral heart scale (VHS) has long been used as an objective standard for evaluation of cardiac silhouette size on thoracic radiographs and plays a key role in the diagnosis as well as the assessment of the severity of canine heart disease. Based on our review of the literature, there has been no published study describing an objective method for measuring overall heart size using computed tomography (CT) in canine patients. The goals of this exploratory prospective method comparison study were to describe a method for objectively evaluating heart size on canine thoracic CT images, determine whether there was a correlation between the VHS when applied to a right lateral thoracic radiograph and a sagittal image of a thoracic CT scan, and determine the effect of cardiac phase on a VHS measured on CT. A method for measuring VHS on canine CT studies was defined. Data were collected on canine patients admitted to The Ohio State Veterinary Medical Center. Each patient received an ECG‐gated thoracic CT immediately followed by a right lateral thoracic radiograph. The VHS was measured on non‐gated, systolic, and diastolic sagittal CT reformatted images. Our results indicated that cardiac gating may not be necessary when assessing canine heart size on CT. When comparing the VHS on gated and non‐gated CT to the VHS on radiographs, there was a moderate to high degree of correlation; however, there was a high degree of variability between CT and radiography.